PERANCANGAN SISTEM INFORMASI ANTRIAN PASIEN DI UPT PUSKESMAS KALIGESING - Damar Eko Cahyono (Politeknik Sawunggalih Aji, 2022)
UPT Puskesmas Kaligesing gets a high number of patients. At that time, its consider less optimal for the service since the queue was too long and the public health center still used manual management. To overcome these problems, a web based patient queue system was needed as a tool in the queue service and data management. The modeling of this system used Unified Modeling Language (UML) tool and used the usecase diagrams, activity diagrams, class diagrams and sequence diagrams. This research resulted a web-based system by using PHP and MySQL. This research resulted a system that can provide solutions to the problems of queue and data management of the patiens.